2019
DOI: 10.1021/acsami.9b17358
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Activated Thermal Transport via Oxide Shell Rupture in Liquid Metal Capsule Beds

Abstract: Liquid metal (LM)-based thermal interface materials (TIMs) have the potential to dissipate high heat loads in modern electronics and often consist of LM microcapsules embedded in a polymer matrix. The shells of these microcapsules consist of a thin LM oxide that forms spontaneously. Unfortunately, these oxide shells degrade heat transfer between LM capsules. Thus, rupturing these oxide shells to release their LM and effectively bridge the microcapsules is critical for achieving the full potential of LM-based T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…In Figure 4b,c, applied pressure is slowly and incrementally increased up to ≈1 MPa while monitoring thermal conductivity throughout. As demonstrated in our prior work, [ 59 ] the dynamics of this incrementally increasing pressure provide insight into the formation of thermal transport pathways via LM deformation and coalescence. Figure 4b illustrates the total thermal resistance during these measurements decreases with increasing pressure and increasing LM content, up to 20 vol%.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In Figure 4b,c, applied pressure is slowly and incrementally increased up to ≈1 MPa while monitoring thermal conductivity throughout. As demonstrated in our prior work, [ 59 ] the dynamics of this incrementally increasing pressure provide insight into the formation of thermal transport pathways via LM deformation and coalescence. Figure 4b illustrates the total thermal resistance during these measurements decreases with increasing pressure and increasing LM content, up to 20 vol%.…”
Section: Resultsmentioning
confidence: 85%
“…This mechanism is described in our prior work on pressure‐activated thermal transport in LM microdroplet beds. [ 59 ] Figure 4b–c illustrates the effects of a gradually increasing pressure on the thermal transport in silicone‐based greases. The main difference between the experiments in Figures 4a and 4b,c is the manner in which pressure is applied.…”
Section: Resultsmentioning
confidence: 99%
“…However, while an electrical interconnection can be established and maintained via one pathway, thermal transmission throughout a material would theoretically require many pathways, as heat transport does not actively take the path of least resistance. This concept was found to be proven correct, as research found that the thermal conductivity increased in proportion to mechanical compression until hitting a peak in pathways and dipping due to an outflow of LM from the deformed material 36 . Similar research around thermal properties enhanced by compression has developed porous elastomer foams wetted by liquid metal via LM‐saturation 126 .…”
Section: Functional Propertiesmentioning
confidence: 94%
“…On one hand, this “native” oxide skin stabilizes the suspension of LM droplets and allows micro‐contact particle mixing and transfer printing 31–33 ; the protective oxide skin assists the processing of LM‐based novel materials. On the other hand, the oxide layer functions as an electron and thermal transport barrier due to its poor conductivity 34–36 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation